2009
DOI: 10.1353/csd.0.0079
|View full text |Cite
|
Sign up to set email alerts
|

The College Persistence Questionnaire: Development and Validation of an Instrument That Predicts Student Attrition

Abstract: The investigators reviewed the retention literature and developed a 53-item questionnaire and tested its validity. Component analysis of the responses of 2,022 students at four schools yielded six reliable factors: Institutional Commitment, Degree Commitment, Academic Integration, Social Integration, Support Services Satisfaction, and Academic Conscientiousness. A second study on 283 first-semester freshmen examined whether factor scores predicted which students returned for their sophomore year. Logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
164
1
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(197 citation statements)
references
References 38 publications
8
164
1
24
Order By: Relevance
“…Institutional commitment has been defined as students' feeling that they made the right institutional choice (Davidson et al, 2009), and more general college student research has shown that it is the most proximal antecedent of undergraduate retention (Bean, 1980;Reason, 2009). Focusing on institutional commitment is consistent with prior calls to have UCCs studying variables consistent with more general academic missions and goals (Archer & Cooper, 1998;Corazzini, 1997).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Institutional commitment has been defined as students' feeling that they made the right institutional choice (Davidson et al, 2009), and more general college student research has shown that it is the most proximal antecedent of undergraduate retention (Bean, 1980;Reason, 2009). Focusing on institutional commitment is consistent with prior calls to have UCCs studying variables consistent with more general academic missions and goals (Archer & Cooper, 1998;Corazzini, 1997).…”
Section: Discussionmentioning
confidence: 89%
“…Previous research (Blau et al, 2015) found an internal consistency reliability of this scale (coefficient alpha) was .92. Institutional commitment was measured using three of four items (Davidson et al, 2009). Items were: "(1) I am sure University X is the right place for me, (2) I am confident that I made the right decision to attend University X, and (3) I have no plans to transfer/leave University X."…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations